Concepts for understanding fruit trees - DeJong, T. M. (Theodore M.) (CABI, CAB International, 2022)
"This book provides a clear set of integrative concepts for understanding how fruit trees work. The emphasis is on overarching principles rather than detailed descriptions of tree physiology or differences among the numerous species of fruit trees"--